Analisis hope pada atlet bulutangkis indonesia juara dunia era ’70 & ’90 - Andangsari, Esther Widhi; Rumondor, Pingkan C.B. (Konsorsium Psikologi Ilmiah Nusantara, 2012)
The present study analyzed a profiling of hope of Indonesian badminton athletes with international achievements. Previous studies have shown that hope was positively related to various outcomes such as sport, academics, physical health, psychological adjustment, and psychotherapy. The participants were consisted of athletes who used to play between 70’s and 90’s. This study utilized a qualitative approach with interpretative phenomenological analysis. Nine mental skills of athletes were used as a guideline of semi-structured interview. The verbatim of interview then analyzed with hope components. Hope was constructed by three components: goals, pathways, and agency thinking. The analysis of participant’s experience showed nine major themes that are: attitude, motivation, goals and commitment, people skills, self talk, mental imagery, managing anxiety, managing emotion, and concentration, with twelve subordinates themes. These themes are similar with high-hope people’s characteristics.